Selenium-Fortified Red Dragon Fruit Dadih Improves Obesity Markers in Rats Induced by a High-Fat, High-Fructose Diet - Safitri, Ulan; Wulandari, Fitri; Mukarromah, Tsamaroh Azzah; Rustanti, Ninik; Pramono, Adriyan (Journal of Health and Nutrition Research, 2025)
Obesity is a growing global health problem linked to metabolic disorders. Functional foods have emerged as a potential non-pharmacological approach to support obesity management. Dadih, a traditional Indonesian fermented buffalo milk product, contains probiotics but has limited antioxidant capacity. This study aimed to evaluate the effects of selenium-fortified red dragon fruit dadih on obesity markers namely body weight and Lee Index and its functional characteristics in rats induced with a high-fat, high-fructose diet (HFFD). A true experimental design with randomized controlled groups was conducted using 24 male Sprague-Dawley rats divided into four groups: healthy control (K−), obesity control (K+), dadih (Di), and selenium-fortified red dragon fruit dadih (Di+). After 28 days of HFFD induction, Di and Di+ groups received 2 mL /200 g BW/day of dadih for 28 days. At the end of the intervention, the Di+ group exhibited significantly moderated body weight gain (from 278.4 ± 3.36 g to 316.6 ± 2.40 g, p = 0.000) and the lowest Lee Index (296.1), compared to Di (329.8 ± 2.58 g to 316.6 ± 2.40 g, Lee Index: 299.0) and K+ (281.2 ± 2.58 g to 364.4 ± 3.50 g, Lee Index: 343.4). Functional analysis showed that Di+ had higher lactic acid bacteria (7.7 × 10⁸ CFU/g) and antioxidant activity (19.54%) than Di. These findings demonstrate that the combination of probiotics, red dragon fruit bioactives, and selenium synergistically improved metabolic regulation. In conclusion, selenium-fortified red dragon fruit dadih improved the functional quality of the product and showed potential to regulate obesity markers. This formulation offers a promising functional food innovation for obesity management and warrants further clinical investigation.